Development of Information Resources in Regional Aspect (Donetsk Region Case Study) - Zakotniuk, O.L. (Економічний вісник Донбасу, 2013)
Territorial quantitative changes in the information component of the regional society were studied in the article. The tendencies and dynamics of information resources development and dissemination were identified and the problems of regional information policy were defined. Досліджено територіальні кількісні зміни інформаційної складової регіонального соціуму. Виявлено тенденції, динаміку розвитку та розповсюдження інформаційних ресурсів, визначено проблеми інформаційної політики регіону. В статье исследованы территориальные количественные изменения информационной составляющей регионального социума. Выявлены тенденции, динамика развития и распространения информационных ресурсов, определены проблемы информационной политики региона.